1994
DOI: 10.1063/1.112123
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of carbon precipitates in GaAs and InP

Abstract: Raman spectra of carbon-doped GaAs and InP show two peaks which are characteristic of C clusters with sp2 bonding. The peaks are seen in C-implanted GaAs and InP following either rapid thermal annealing or furnace annealing. The peaks are also seen in heavily doped epilayers following furnace annealing. Various mechanisms for C precipitation are discussed. Experimental evidence suggests that the loss of the group V component at the surface during annealing may play a role in the precipitation of C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…Ab initio local density functional theory (LDF) predicts that the defect is a deep donor and that ͑ 12 C-12 C͒ 1 pairs in AlAs give rise to a Raman active stretch mode at a frequency of 1590 cm 21 and an infrared (IR) active E mode at 443 cm 21 [8]: we show that the corresponding frequencies for the analogous defect in GaAs are predicted to be 1798 and 329 cm 21 . To date, only broad bands at 1355 and 1585 cm 21 have been observed in Raman spectra of annealed GaAs following ion implantation with 12 C [10]. These features correspond to the D and G bands of sp 2 bonded graphitic carbon particles, and they shift to lower energies when samples are implanted with 13 C, rather than 12 C, confirming the proposed assignment.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…Ab initio local density functional theory (LDF) predicts that the defect is a deep donor and that ͑ 12 C-12 C͒ 1 pairs in AlAs give rise to a Raman active stretch mode at a frequency of 1590 cm 21 and an infrared (IR) active E mode at 443 cm 21 [8]: we show that the corresponding frequencies for the analogous defect in GaAs are predicted to be 1798 and 329 cm 21 . To date, only broad bands at 1355 and 1585 cm 21 have been observed in Raman spectra of annealed GaAs following ion implantation with 12 C [10]. These features correspond to the D and G bands of sp 2 bonded graphitic carbon particles, and they shift to lower energies when samples are implanted with 13 C, rather than 12 C, confirming the proposed assignment.…”
supporting
confidence: 48%
“…We note that the frequency of the line from 12 C-12 C pairs at 1742 cm 21 is comparable with that of a double bonded C--C structure that has a characteristic frequency of 1650 cm 21 in molecules [14]. Two of our samples doped with 12 C and 13 C, respectively, showed broad bands at ϳ1600 and 1370 cm 21 due to sp 2 -bonded clusters of 12 C [10]. We attribute these bands to surface contamination because of the lack of an isotopic shift.…”
mentioning
confidence: 71%
“…In addition to the GaN E2 and A1 (LO) phonon modes, a strong band is observed centered around 1350 cm À1 . This frequency corresponds to sp 2 bonded carbon and has previously been correlated with carbon clusters in GaAs [20,21] and also in GaN [22]. A doping level exceeding the solid solubility limit of carbon in GaN could act as a driving force for carbon clustering/precipitation in very heavily doped layers, as suggested in Ref.…”
Section: Mechanism Of Carbon Incorporation In Ganmentioning
confidence: 91%
“…Recently, Moll et al reported the observation of sp 2 -type bonding of carbon atoms in Raman spectra from annealed carbon-implanted and carbon-doped GaAs films, suggesting the precipitation of supersaturated carbon atoms into graphite after annealing. 10 Since the heavy carbon doping results in lattice mismatch with the GaAs substrate, 11,12 it is important to study the strain relaxation and the behavior of misfit dislocations upon thermal annealing for device applications. In this letter, we report on the effects of annealing on misfit dislocations and the interesting observation of overrelaxation of misfit strain in heavily carbon-doped GaAs films.…”
mentioning
confidence: 99%